Clinicopathological and molecular subtypes of breast cancer in the Eastern Cape, South Africa: A two-year retrospective study - Hayden Gerald Kretzmann; Oladele Vincent Adeniyi (PLoS ONE, 2025)
Background Breast cancer (BC) is the most common cancer in women worldwide and the most frequent cause of cancer death in women in low- and middle-income countries (LMIC). The incidence of BC in Africa is on the rise, expected to double by 2050, primarily owing to late presentation and weak health infrastructure in sub-Saharan Africa (SSA). This study addresses the lack of recent data on BC cases in the Eastern Cape Province of South Africa. Objective The objectives of this study were to describe the clinicopathological characteristics and molecular subtypes of BC and, in addition, to examine the association between the clinicopathological characteristics and the molecular subtypes of BC in a single tertiary hospital in the Eastern Cape Province of South Africa. Methods A two-year (2022–2023) retrospective cross-sectional clinical record review study was conducted on patients treated for invasive BC at a tertiary hospital in the Eastern Cape Province, South Africa. The demographic, clinical and pathological characteristics and molecular subtypes were reported. Associations were investigated between the BC molecular subtypes identified and the clinicopathological characteristics of the patients. Results A total of 282 patients met the study’s inclusion criteria. Most patients were female (98.6%) and African (88.1%). The mean age of the patients was 58.7 years, with BC most prevalent in the age group >70 (25.2%) and postmenopausal (77.4%). Breast lump was the most common presenting complaint (98.6%), with 61% of patients presenting three months after noticing the anomaly. The most common tumour size (59.4%) was > 5 cm (mean = 6.37 ± 3.6), with the most common clinical T stage being T4 (50.4%). Lymph node involvement was seen in 50.4% of cases. Patients mostly presented in Stages III and IV of the disease (60.1%). Invasive ductal carcinoma not otherwise specified (NOS) was the most common histopathological subtype (86.2%). Grade 2 (56.2%) and Grade 3 (29.5%) BC accounted for the majority of cases. Luminal B was found in 47.4% of cases, Luminal A in 28.5%, triple negative breast cancer (TNBC) in 18.6% and human epidermal growth factor receptor 2 (HER2) enriched in 5.5% of cases, respectively. Conclusion In our setting, most patients consulted at a late stage of the disease with a large tumour size, positive lymph node status and a high histological grade. Luminal B tumours are the most common molecular subtype. These results indicate the need for more intensive breast cancer awareness campaigns, early detection, and timely referral and treatment.